Bandwidth allocation games based on network selection for video communication - Shu-zhi WEI; Qi ZHU (Tongxin xuebao)
A bandwidth allocation game based on network selection (BAG-NS) was proposed for video communication in heterogeneous wireless networks.Firstly,according to the video characteristics of different users and current network conditions,the algorithm calculated the weights of network factors and selected the optimum network by combining analytic hierarchy process and entropy theory.Secondly,the user’s utility function with payoff and cost was designed,and a distributed iterative algorithm is used to obtain the Nash equilibrium.Then the existence and uniqueness of the Nash equilibrium are proved.Simulation results show that the proposed algorithm enables different users to reasonably distribute in different networks and takes users’ fairness and network congestion control into consideration,which increases the utilization of network resources,reduces the users’ video distortion,and improves the users’ video quality.